2021
DOI: 10.1016/j.xcrp.2021.100391
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state packing dictates the unexpected solubility of aromatic peptides

Abstract: Summary The understanding and prediction of the solubility of biomolecules, even of the simplest ones, reflect an open question and unmet need. Short aromatic tripeptides are among the most highly aggregative biomolecules. However, in marked contrast, Ala-Phe-Ala (AFA) was surprisingly found to be non-aggregative and could be solubilized at millimolar concentrations. Here, aiming to uncover the underlying molecular basis of its high solubility, we explore in detail the solubility, aggregation propen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 66 publications
(34 reference statements)
2
3
0
Order By: Relevance
“…Moreover, the solubility of tyrosine is significantly increased by the addition of EGCG, which interferes with the aromatic interactions between the tyrosine building blocks in their insoluble arrangement. [56] This discovery is also consistent with the established effect of solid-state packing on the solubility of ultrashort peptides. [57] Moreover, other studies have shown the ability of arginine to increase the solubility of metabolites, and specifically nucleobases, [57] in line with the well-established role of arginine in increasing the solubility of proteins.…”
Section: Methodssupporting
confidence: 80%
See 1 more Smart Citation
“…Moreover, the solubility of tyrosine is significantly increased by the addition of EGCG, which interferes with the aromatic interactions between the tyrosine building blocks in their insoluble arrangement. [56] This discovery is also consistent with the established effect of solid-state packing on the solubility of ultrashort peptides. [57] Moreover, other studies have shown the ability of arginine to increase the solubility of metabolites, and specifically nucleobases, [57] in line with the well-established role of arginine in increasing the solubility of proteins.…”
Section: Methodssupporting
confidence: 80%
“…A recent study revealed that this property is related to the dimeric organization of tyrosine in the solid‐state as determined by X‐ray crystallography. Moreover, the solubility of tyrosine is significantly increased by the addition of EGCG, which interferes with the aromatic interactions between the tyrosine building blocks in their insoluble arrangement [56] . This discovery is also consistent with the established effect of solid‐state packing on the solubility of ultrashort peptides [57] .…”
Section: Unravelling “Metabolostasis”: How Do Cells Maintain Metaboli...supporting
confidence: 78%
“…The torsion angles around the N-terminal Phe residue appeared to be consistent within the helical arrangement, with dihedral angles (ϕ, ψ) having values of −102.54 and 149.23, respectively (Figure S14). Ben-FF prepared from the d -form of amino acid, i.e., Ben- D F D F, resulted in inverted handedness of the helix assembly. These supramolecular chirality results are in good agreement with our conclusion of aryl handedness from CD spectra of Ben-FF/PEG hydrogels.…”
Section: Resultsmentioning
confidence: 99%
“…Soft ionisation techniques such as ESI have been shown to preserve non‐covalent interactions in small molecules, peptides, and proteins. However these MS data are obtained from a high energy gas‐phase state, thus we also sought to gauge the propensity of each tag to engage in non‐covalent interactions which might affect crystal stability and dissolution [23,24] . The crystal structure of 1,4‐diphenyl‐1,3‐butadiyne has been solved, [25] however, to our knowledge 1 a – 1 f have never been investigated by X‐ray crystallography.…”
Section: Resultsmentioning
confidence: 99%